2022
DOI: 10.35812/cellulosechemtechnol.2022.56.24
|View full text |Cite
|
Sign up to set email alerts
|

"Formation of Hydrogels From Antioxidative Synthetic Hydroxycinnamate Ester Conjugates Based on Corn Bran Arabinoxylan "

Abstract: Corn bran arabinoxylan (CAX) was extracted from corn bran and modified through conjugating to four hydroxycinnamic acids (HAs), namely ferulic acid (FA), p-coumaric acid (p-CA), caffeic acid (CA), and sinapic acid (SA). These HA arabinoxylan esters (HA-CAX-n) exhibited analogous n-degrees of substitution (DS), FA-CAX-0.31, p-CA-CAX-0.32, CA-CAX-0.32, and SA-CAX-0.31. The antioxidant capacity was evaluated by a chemical method – an oxygen radical antioxidant capacity (ORAC) assay – and cellular models – a cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In other types of esterification reactions, Li [ 69 ], for example, used four kinds of hydroxycinnamic acids (FA, p-CA, SA, CA) to modify arabinoxylan (CAX) extracted from corn bran through esterification reactions. The study found that CA-CAX-0.32, which contains more phenolic hydroxyl groups and hydrogen ions, exhibits antioxidant properties and can inhibit oxidative damage to cells caused by free radicals.…”
Section: Modification Of Gobpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other types of esterification reactions, Li [ 69 ], for example, used four kinds of hydroxycinnamic acids (FA, p-CA, SA, CA) to modify arabinoxylan (CAX) extracted from corn bran through esterification reactions. The study found that CA-CAX-0.32, which contains more phenolic hydroxyl groups and hydrogen ions, exhibits antioxidant properties and can inhibit oxidative damage to cells caused by free radicals.…”
Section: Modification Of Gobpsmentioning
confidence: 99%
“…The laccase catalyzed the oxidative cross-linking of ferulic acid groups to form covalent di-ferulic acid cross-links, producing strong hydrogels. Li [69] used laccase (derived from Trichoderma and oyster mushrooms) as a cross-linker to cross-link hydroxycinnamic-acid-esterified corn bran arabinoxylan at 25 • C. The author noted that methoxy and hydroxyl groups provide a higher cross-linking density, and the hydrogels exhibited good mechanical properties and biocompatibility, with broad application prospects in antioxidant skincare products and functional foods. Yilmaz-Turan et al [114] extracted arabinoxylan (FAX) from wheat bran and formed functional hydrogels through laccase oxidative cross-linking.…”
Section: Gobp Hemicellulose In Hydrogel Formationmentioning
confidence: 99%